TARGETED BIOLOGICS IN CHILDHOOD ATOPIC DERMATITIS: A COMPREHENSIVE REVIEW OF IMPACT AND INNOVATION - Darya Lazitskaya,; Dmytro Kowalczuk,; Mykola Sobchynskyi,; Andrzej Myrny,; Wiktoria Kasianik,; Kamil Turlej,; Valeryia Milasheuskaya,; Iga Kiełbaszewska,; Natalia Surosz,; Katsiaryna Miraniuk,; Dawid Wiczkowski, (International Journal of Innovative Technologies in Social Science, 2025)
Atopic dermatitis (AD) is a prevalent chronic inflammatory skin disease in children that significantly impairs their quality of life and can be linked to other allergic disorders. Current treatments for paediatric AD are not always effective, but biologics hold promise as they work on the key factors behind inflammation.Dupilumab, a fully human monoclonal antibody that inhibits IL-4 and IL-13 signalling by binding to the IL-4 Rα subunit, has shown good efficacy and an acceptable safety profile in treating infants and children with moderate-to-severe AD. It is now registered for the treatment of moderate-to-severe AD in paediatric patients, including young children and infants as young as six months in some regions.Researchers are continuing to look at how safe and effective dupilumab is for children of different ages with atopic dermatitis, and whether starting treatment early can change how the disease develops over time. Other biologic treatments such as tralokinumab (which blocks IL-13), lebrikizumab, nemolizumab, tezepelumab, and JAK inhibitors are also being studied, and some have already been approved for use in children. Together, these therapies are expanding the options available for managing paediatric AD. In this review, we highlight the latest evidence on biologics in children, focusing on how they work, how well they control disease, and what is known about their safety, to help support treatment decisions in practice.Aim of Study: We aim to review current understanding of atopic dermatitis and the latest developments in targeted therapies, including biologics and small-molecule inhibitors, based on clinical trial findings.